BENTUK PASAR DALAM TEORI EKONOMI MIKRO DAN EKONOMI MIKRO ISLAM - Misbahul Khoir; Khozinul Ulum; Imam Wahyudhi (Journal of Islamic Banking, 2023)
A market is the meeting point of demand and supply to facilitate buying and selling transactions. Based on their structural forms, markets are categorized into two types: Perfect Competition and Imperfect Competition. Monopoly, as defined by anti-monopoly laws, involves the control of production, marketing of goods, and/or the use of specific services by a single business entity or a group of business entities. Oligopoly is a form of market competition dominated by a few producers or sellers within a specific geographical area. Monopolistic competition is characterized by numerous producers generating similar commodities with varying characteristics. Oligopsony refers to a market condition where only a few buyers face many sellers. The objective of this journal is to impart knowledge to readers regarding the various forms of markets.